Research on the Relationship between Exposure to Dioxins and Cancer Incidence in Vietnam - Tuong Phi Vuong (Toxics, 2022)
The aim of this literature review is to discover whether there is a relationship between exposure to dioxins and cancer incidence in the hotspot regions of Vietnam by estimating the risk ratio index. The results of the study show that the incidence of cancer (soft tissue sarcoma; Hodgkin’s and non-Hodgkin’s lymphoma; lung, prostate, and liver cancer) in the dioxin-exposed Vietnamese population is much higher than the results of studies published in other countries because of the high levels of dioxins in South Vietnam, where Agent Orange was sprayed during the war. Further studies on the health effects of dioxins in the Vietnamese population, including cancer incidence, should be conducted with improved research methods.